THE BLOOM MODEL AND ITS IMPACT ON THE DEVELOPMENT OF THE STABBING SKILL OF THE FENCING SWORD PLAYERS IN MISAN GOVERNORATE (American Journal of Research in Humanities and Social Sciences, 2023)
Fencing is one of the sports whose development has been influenced by other sciences because it is one of the sports that prioritizes fundamental abilities as a necessary foundation for growth. As a result, coaches devote a significant amount of time to teaching players these abilities, especially the stabbing technique, which is the game's foundation and allows players to take a touch by directing the weapon. As the problem of the research was that most players need an auxiliary model that harmonizes with their weaknesses, the idea of using and harnessing the model (Bloom) to achieve a level of better skill performance to reach the appropriate performance or close to the ideal, and its contents of steps contribute to mastering the skill of stabbing with a fencing sword weapon because it is one of the important skills in this sport. The objective of this research is to examine the influence of the Bloom model on the enhancement of fencing sword stabbing skills in Misan Governorate. The researcher hypothesizes that there are notable disparities between the pre- and post-test results of the two research groups, with the experimental group, which utilizes the Bloom model, exhibiting superior performance. To investigate this, an experimental approach was employed, involving two comparable groups - an experimental group and a control group. Both groups underwent pre- and post-tests to evaluate their skill development. The research sample consisted of fencing athletes from the clubs in Misan Governorate for the sports season (2022-2023). The sample size comprised 18 players, who were selected deliberately. The distribution of sample members was conducted randomly using a drawing method. Specifically, 8 players were assigned to the control group, 8 players to the experimental group, and 2 players to the exploratory experiment. The results were extracted using statistical software (SPSS) and based on the findings of the study, several conclusions were drawn. One of the notable findings was that the group that followed the Bloom model demonstrated significant improvement in acquiring the skill of stabbing. This can be attributed to the model's effectiveness and compatibility with performance. Consequently, the researcher recommended the adoption of the Bloom model for teaching fundamental skills, particularly the skill of stabbing in fencing. This model is considered distinctive and suitable for learners' capabilities and abilities.